Evolution of the Mineralocorticoid Receptor and Gender Difference in Cardiovascular Pathology - Zuccalà, Alessandro (Journal of Cardiology and Cardiovascular Medicine, 2025)
Retracing the evolution of Mineralocorticoid Receptors (MR) obliges us to take an instructive as well as fascinating leap back in time. This journey teaches us that the relationship between MRs and what we consider their natural ligand, aldosterone, has not always been an exclusive one. MRs operated for a very long time in the oceans and, in any case, in an aquatic environment, stimulated by ligands other than aldosterone, and exercising functions that we still do not know well but which were certainly different from those they currently perform in terrestrial vertebrates, where they maintain normal sodium and body fluids. The history of MRs was initially intertwined with that of female sexual hormones, in particular with progesterone, which was one of the first agonists for MRs, before becoming, with the transition to the terrestrial environment, an important antagonist. This initial intertwining could be the cause of the sexual dimorphism that can be glimpsed when these receptors are overstimulated, as emerges from many experimental studies and some clinical data and/or when antagonistic drugs for these receptors are studied. This must be taken into account in the planning of clinical studies, especially randomized controlled trials, in which the presence of the two sexes must always be well balanced and in the interpretation of the results which must always be performed being well aware of the gender of participants. This does not always happen, however.